‘Freedom Through Marketing’ Is Not Doublespeak - Shabbir, Haseeb; Hyman, Michael; Dean, Dianne; Dahl, Stephan (Journal of Business Ethics, 2020)
The articles comprising this thematic symposium suggest options for exploring the nexus between freedom and unfreedom, as exemplified by the British abolitionists’ anti-slavery campaign and the paradox of freedom. Each article has implications for how these abolitionists achieved their goals, social activists’ efforts to secure reparations for slave ancestors, and modern slavery (e.g., human trafficking). We present the abolitionists’ undertaking as a marketing campaign, highlighting the role of instilling moral agency and indignation through re-humanizing the dehumanized. Despite this campaign’s eventual success, its post-emancipation phase illustrates a paradox of freedom. After introducing mystification as an explanation for the obscuring rhetoric used to conceal post-emancipation violations of freedom during the West’s colonial phase, we briefly discuss the appropriateness of reparations. Finally, we discuss the contributions made by the articles in this thematic symposium.
Journal of Business Ethics 'Freedom through Marketing' is not Doublespeak –Manuscript Draft–Manuscript Number: Article Type: Original Paper Full Title: 'Freedom through Marketing' is not Doublespeak Section/Category: Others Corresponding Author: Michael R Hyman, Ph.D. New Mexico State University Las Cruces, NM UNITED STATES Corresponding Author E-Mail: Order of Authors:
Keywords: Paradox of freedom; Anti-slavery campaigns; Abolition; Transatlantic slave trade; Reparations; Mystification; Ethical blindness; Human trafficking